2020
DOI: 10.3390/molecules26010079
|View full text |Cite
|
Sign up to set email alerts
|

TiCl4 Dissolved in Ionic Liquid Mixtures from Аb Initio Molecular Dynamics Simulations

Abstract: To gain a deeper understanding of the TiCl4 solvation effects in multi-component ionic liquids, we performed ab initio molecular dynamics simulations of 1-butyl-3-methylimidazolium [C4C1Im]+, tetrafluoroborate [BF4]−, chloride [Cl]− both with and without water and titanium tetrachloride TiCl4. Complex interactions between cations and anions are observed in all investigated systems. By further addition of water and TiCl4 this complex interaction network is extended. Observations of the radial distribution funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(45 citation statements)
references
References 85 publications
5
40
0
Order By: Relevance
“…The main goal of our investigations was to get insight into the reaction mechanisms of the IL-based synthesis of Ti(OH)OF• 0.66H 2 O, especially the role of the BF 4 − anion and the formation of Ti complexes, on the basis of NMR spectra. To understand the interactions of the reactants with each other, the composition of mixtures of the involved compounds was systematically varied, and these solutions were subjected to 1 H, 13 C, 19 F, and 11 B NMR measurements. A scheme showing all measured solutions and the questions we tried to answer with different NMR measurements can be found in the Supporting Information (SI) (see Scheme S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main goal of our investigations was to get insight into the reaction mechanisms of the IL-based synthesis of Ti(OH)OF• 0.66H 2 O, especially the role of the BF 4 − anion and the formation of Ti complexes, on the basis of NMR spectra. To understand the interactions of the reactants with each other, the composition of mixtures of the involved compounds was systematically varied, and these solutions were subjected to 1 H, 13 C, 19 F, and 11 B NMR measurements. A scheme showing all measured solutions and the questions we tried to answer with different NMR measurements can be found in the Supporting Information (SI) (see Scheme S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the past, NMR spectroscopy has already been successfully used to investigate IL-based syntheses. 13 Saihara et al investigated the hydrolysis process of the IL N,N-diethyl-Nmethyl-N-(2-methoxyethyl)ammonium tetrafluoroborate (DEME BF 4 − ) in the presence of water by means of 19 F and 11 B NMR measurements. 14 They found that during the hydrolysis of BF 4 − , HF is generated and reacts with the surrounding glass container since SiF 6 2− was detected in the 19 F NMR spectrum.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, ionic liquids (and DESs) have been studied computationally mainly from classical molecular dynamics simulations based on force fields. Car–Parrinello or Born–Oppenheimer ab initio molecular dynamics (AIMD) simulations based on the explicit description of the electronic structure concerning ionic liquids , and deep eutectic solvents , also appeared in the literature. Many contributions and clarifications came from static quantum chemical calculations. As usual in static quantum chemistry, density functional theory (DFT) serves as workhorse for many calculations; , however, different methods were applied as well. Polarizable force fields in all forms receive always special attention because they overcome many problems of traditional MD simulations. …”
Section: Introductionmentioning
confidence: 99%
“…8 Traditionally, ionic liquids (and DESs) have been studied computationally mainly from classical molecular dynamics simulations based on force fields. 9−22 Car−Parrinello or Born−Oppenheimer ab initio molecular dynamics (AIMD) simulations 23 based on the explicit description of the electronic structure concerning ionic liquids 24,25 and deep eutectic solvents 8,26−30 also appeared in the literature. Many contributions and clarifications came from static quantum chemical calculations.…”
Section: ■ Introductionmentioning
confidence: 99%